Star Trek Warps to an End. - Lileks, James (American Enterprise)
Spring 2005 saw the end of science-fiction's most successful franchise as Star Trek went off air for good forty years after its pilot debut. A summary is provided of four decades of the television show to determine what each series—“The Original Series”, “The Next Generation”, “Deep Space Nine”, “Voyager”, and “Enterprise”—reflects of the zeitgeist that produced it.